An Isoelastic Monoblock Cup Retains More Acetabular and Femoral Bone Than a Modular Press-Fit Cup: A Prospective Randomized Controlled Trial. (2nd June 2021) - Brodt, Steffen; Jacob, Benjamin; Nowack, Dimitri; Zippelius, Timo; Strube, Patrick; Matziolis, Georg
Abstract : Background: For cup revision after total hip arthroplasty, sufficiently good periacetabular bone stock is a prerequisite for fixation of the revision implant. Cementless cups can lead to a relevant reduction of peri-implant bone mineral density (BMD) through stress-shielding. Methods: Fifty patients were included in this prospective randomized controlled trial. Group 1 (RM group) received an isoelastic monoblock cup (RM Pressfit vitamys; Mathys). Group 2 (IT group) received a modular titanium cup (Allofit-S IT Alloclassic with a polyethylene liner; Zimmer). Periacetabular BMD was determined and subdivided into 4 regions of interest by dual x-ray absorptiometry at 1 week (baseline) and at 4 years postoperatively. Our primary outcome was reduction in periacetabular BMD. Results: Periacetabular BMD was reduced by an average of 15.1% in the RM group and 16.5% in the IT group at 4 years postoperatively. No significant difference was found between the 2 groups over the periacetabular structure as a whole. However, the decrease of BMD in the polar region was significantly different in the RM group (4.9% ± 10.0%) compared with the IT group (15.9% ± 14.9%, p = 0.005). Use of the isoelastic RM cup showed significantly less bone loss than the modular IT cup. Conclusions: Relevant loss of BMD at 4 years after surgery was identified in the periacetabular region in both groups. No differences between the 2 cup systems were found when looking at the overall periacetabular region. As a secondary outcome, less postoperative periacetabular bone loss occurred in the polar region when an isoelastic cup was used. Longer follow-up is required to allow for conclusions to be drawn about the long-term course of the 2 cup systems. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.